2021
DOI: 10.3390/pharmaceutics13071066
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Indigoidine Synthesis as a High-Throughput Colourimetric Screen for Antibiotics Targeting the Essential Mycobacterium tuberculosis Phosphopantetheinyl Transferase PptT

Abstract: A recently-validated and underexplored drug target in Mycobacterium tuberculosis is PptT, an essential phosphopantetheinyl transferase (PPTase) that plays a critical role in activating enzymes for both primary and secondary metabolism. PptT possesses a deep binding pocket that does not readily accept labelled coenzyme A analogues that have previously been used to screen for PPTase inhibitors. Here we report on the development of a high throughput, colourimetric screen that monitors the PptT-mediated activation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Of various biochemical assays to measure PpTase activity ( 9 , 17 , 22 , 23 ), we opted for fluorescence polarization (FP)-based assay introduced for the surfactin synthetase activating protein Sfp, a PpTase from Bacillus subtilis ( 24 ). We used the N-terminal ACP domain of Mtb polyketide synthase 13 (N-ACP PKS13) as a cosubstrate (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of various biochemical assays to measure PpTase activity ( 9 , 17 , 22 , 23 ), we opted for fluorescence polarization (FP)-based assay introduced for the surfactin synthetase activating protein Sfp, a PpTase from Bacillus subtilis ( 24 ). We used the N-terminal ACP domain of Mtb polyketide synthase 13 (N-ACP PKS13) as a cosubstrate (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous in vitro molecular target-based HTS assays using the SML are reported to date that successfully identified inhibitors of various protein targets such as penicillin-binding protein (PBP) [ 178 ], mitogen-activated protein kinase (MKK) [ 179 ], the type III secretion system (T3SS) [ 180 ], the anthrax lethal factor (LF) [ 181 ], phosphopantetheinyl transferase (PPTase) [ 182 ], peptidoglycan O-acetyltransferase [ 183 ], telomere resolvase (ResT) [ 184 ], etc. Spicer et al screened ~292,000 compounds against M18 Aspartyl Aminopeptidase (PfM18AAP) and identified two compounds that were also active in whole cell-based assays [ 185 ].…”
Section: Synthetic Molecule Library (Sml) Screening For Antibacterial...mentioning
confidence: 99%
“…1 b) that kills M. tuberculosis by inhibiting PptT in vitro and in a mouse model, with no toxicity to human cells, contributed to redefine PPTases as major contributors to the development of antimycobacterial agents 11 . This motivated the recent development of a simple high-throughput colorimetric assay to directly screen for inhibitors of PptT 12 .…”
Section: Introductionmentioning
confidence: 99%